Inuit Throat-Games and Siberian Throat Singing: A Comparative, Historical, and Semiological Approach - Nattiez, Jean-Jacques (Ethnomusicology, 1999)

De l’oreille au cœur. Naissance du chant religieux en langues amérindiennes dans les missions de Nouvelle-France, 1600-1650 - Dubois, Paul-André (Septentrion, 1997)

Naissance du cantique en langue vernaculaire dans les missions de Nouvelle-France et conquête des langues amérindiennes : une relation - Dubois, Paul-André (Recherches amérindiennes au Québec, 1997)

A Bosnian Sephardic Woman in Kahnewake, Quebec - Cohen, Judith R. (Canadian Woman Studies/Les cahiers de la femme, 1996)

Naissance et évolution de la musique religieuse en langue vernaculaire dans les missions amérindiennes de Nouvelle-France au cours de la première moitié du XVIIième siècle - Dubois, Paul-André (Université Laval, 1996)

Visions of Sound: Musical Instruments of First Nation Communities in Northeastern America - Diamond, Beverley; Cronk, M. Sam; Rosen, Franziska von (University of Chicago Press, 1995)

Quebec Sings "E Uassiuian": The Coming of Age of a Local Industry - Grenier, Line; Morrison, Val (Popular Music: Style and Identity, 1995)

"Echoes of a Proud Nation": Reading Kahnawake's Powwow as a Post-Oka Text - Blundell, Valda (Canadian Journal of Communication, 1993)
Abstract: After presenting one history of North American powwows as sites where aesthetic forms are deployed to transform meanings about aboriginal peoples, an analysis is offered of the powwow produced by the Kahnawake Mohawk a year after their involvement in the Oka crisis. Résumé: Cet article présente d'abord une histoire des powwows nord-américains comme lieux de déploiement de formes esthétiques qui modifient le sens et la signification des peuples autochtones. L'article analyse ensuite le powwow des Mohawks de Kahnawake qui a eu lieu un an après la crise d'Oka.
Keywords: Cultural producers

Alanis Obomsawin - Kivi, K. Linda (Canadian Women Making Music, 1992)

“La Mariouche est pour un blanc” (Jack Monoloy). À propos de la question des minorités dans la chanson canadienne-française - Mathis, Ursula (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 1992)

Voces Cantantes in Vestro: History of Research on Music among the Wabanaki - Morrison, Ann (Papers of the Algonquian Conference / Les Actes du Congrès des Algonquinistes, 1991)

"Not knowing" and the study of Native music cultures: Introductory comments - Diamond Cavanagh, Beverley (Ethnomusicology in Canada, 1990)

Music and gender in the sub-arctic Algonkian area - Diamond, Beverley (Women in North American I[*****] Music: Six Essays, 1989)

Le plain-chant chez les Amérindiens - Dubois, Paul-André (Grégoriana, 1989)
Keywords: Pas de lien web

The Morphology and Phonology of Katajjait (Inuit Throat Games) - Bagemihl, Bruce (Canadian Journal of Linguistics/Revue canadienne de linguistique, 1988)
A linguistic theory can be considered to have explanatory force if it may be extended to a body of facts considerably beyond the domain for which it was originally conceived. In general, the further the new domain is from the original, the greater the support that accrues to that theory. In this paper, a number of developments within current morphological and phonological theory will be utilized in the analysis of an extraordinary form of vocal behaviour, the katajjait (sg. katajjaq) or throat games of the Canadian Inuit. The result will be a revealing account of the structures of these katajjait, as well as a remarkable confirmation of principles of linguistic theory from a domain which has been hitherto unreported in the linguistic literature.

The Transmission of Algonkian Indian Hymns: Between Orality and Literacy - Cavanagh, Diamond (Musical Canada: Words and Music Honouring Helmut Kallmann, 1988)

Sémiologie des jeux vocaux Inuit - Nattiez, Jean-Jacques (Semiotica, 1987)
Keywords: Pas de lien web

Hymn Anomalies in Traditional Cree Song - Whidden, Lynn (Recherches amérindiennes au Québec, 1987)

An Ethnomusicological Study of the Traditional Songs of the Chisasibi Cree - Whidden, Lynn (Université de Montréal, 1986)

Une approche sémiologique du powwow contemporain canadien - Blundell, Valda (Recherches amérindiennes au Québec, 1985)

Les mythes et la musique naskapis - Cavanagh, Diamond (Recherches amérindiennes au Québec, 1985)

Le disque de musique amérindienne, IV. Nouveaux disques et cassettes de musique inuit - Nattiez, Jean-Jacques (Recherches amérindiennes au Québec, 1985)

Transformations musicales et culturelles chez les Cris de l’Est - Preston, Richard J. (Recherches amérindiennes au Québec, 1985)

Les hymnes, une anomalie parmi les chants traditionnels des Cris du Nord - Whidden, Lynn (Recherches amérindiennes au Québec, 1985)

Un projet d'éducation musicale à Wemindji, Québec - Whidden, Lynn (Recherches amérindiennes au Québec, 1985)

Musique inuit au Québec arctique : contribution à une méthode d'analyse en anthropologie de la musique - Montpetit, Carmen; Veillet, Céline (Les Cahiers de l'ARMuQ, 1984)

Some Aspects of Inuit Vocal Games - Nattiez, Jean-Jacques (Ethnomusicology, 1983)

The Rekkukara of the Ainu (Japan) and the Katajjaq of the Inuit (Canada): A Comparison - Nattiez, Jean-Jacques (The World of Music, 1983)

Traditional Cree Song and the Problem of Creativity in Music - Whidden, Lynn (Actes du quatorzième congrès des algonquinistes, 1983)

Comparisons within a Culture: The Example of the Katajjaq of the Inuit - Nattiez, Jean-Jacques (Cross-Cultural Perspectives on Music, 1982)

Le disque de musique amérindienne, III. La musique indienne sur disque : cent ans d’ethnomusicologie - Nattiez, Jean-Jacques (Recherches amérindiennes au Québec, 1981)

An Introduction to the Music of the Malecite Indians - Baskin, Suzan Ruth (Université Carleton, 1980)

Pour l'adéquation de la transcription en ethnomusicologie : l'exemple du katajjaq - Berthiaume-Zavada, Claudette (Canadian University Music Review, 1980)
Keywords: Music

Le disque de musique amérindienne, II. Introduction à l’écoute des disques de musique inuit - Nattiez, Jean-Jacques (Recherches amérindiennes au Québec, 1980)

The Fiddlers of James Bay - Rodgers, Bob (Office national du film du Canada, 1980)
This short documentary traces the history of the fiddle’s arrival in Canada 300 years ago via Scottish traders from Orkney Island. The Cree population of what is now Northern Québec adopted the instrument, and many contemporary Cree residents are master fiddlers. In this film, two Cree fiddlers travel to the Orkney Islands, the birthplace of the music they learned from their fathers and grandfathers. The film captures the warmth and good will of this reunion.

Musique inuit du Québec arctique : contribution à une méthode d'analyse en anthropologie de la musique - Montpetit, Carmen (Université Laval, 1979)

Le katajjaq : un jeu inuit traditionnel - Beaudry, Nicole (Études Inuit Studies, 1978)
Katajjaq, a traditional Inuit game Katajjait — the traditional Inuit throat-games — display unusual musical properties and for that reason they have been submitted to extensive musicological analysis. Furthermore, they also constitute a particularly rich example of traditional Inuit game behaviour. The present article aims at backing that statement through an analysis of Inuit games from Central Arctic, based on available written information¹.This analysis enables us to define the katajjaq not only in terms of formal properties, but also in terms of social functions. This analytical definition is achieved by comparing katajjaq with some of the Inuit game mechanisms. le katajjaq, un jeu inuit traditionnel Le katajjaq ou jeu de gorge inuit à l'origine lointaine, se caractérise par des propriétés musicales exceptionnelles. Ce jeu vocal a donc fait l'objet d'analyses musicologiques approfondies. Par ailleurs, il illustre particulièrement bien le système ludique inuit traditionnel. Nous cherchons ici à confirmer cette hypothèse, à la suite d'une étude par les textes¹ sur les jeux inuit de l'Arctique central en général. A la lumière de cette étude, nous tâchons de définir le jeu de gorge, tant par ses fonctions sociales que par son comportement formel et ce, en comparaison avec quelques mécanismes des jeux inuit traditionnels.

Toward Transcription and Analysis of Inuit Throat-Games: Macro-Structure - Beaudry, Nicole (Ethnomusicology, 1978)

Toward Transcription and Analysis of Inuit Throat-Games: Micro-Structure - Charron, Claude (Ethnomusicology, 1978)

Le disque de musique amérindienne, I. Le disque de tradition orale et ses problèmes - Nattiez, Jean-Jacques (Recherches amérindiennes au Québec, 1978)

Entre cri et chant. Les katajjait, un genre musical féminin - Saladin d'Anglure, Bernard (Études/Inuit/Studies, 1978)
The growing popularity in the West of various graphic or plastic expressions of contemporary (or prehistoric) Inuit art has overshadowed other aspects of Inuit art — particularly traditional music, within which throat games represent a most fascinating genre. Indeed, some of the first western travelers who attended a katajjaq performance were to pay a high price to have their curiosity satisfied — as we shall see in the following documents. The anthropologist cannot escape this fascination either, for the katajjait constitute a complex and ambiguous genre, belonging to cry and language, song and dance, game and music, ritual and performance, expressing Inuit symbolism on the relationship between man and woman, the relationship to nature and the supernatural and reflecting elements of the social structure since the performance of katajjait requires cooperation and sometimes gives rise to competition between performers. Le succès croissant en occident des différentes expressions graphiques ou plastiques de l'art inuit contemporain (ou préhistorique) a masqué d'autres aspects de l'art inuit, en particulier l'art musical traditionnel au sein duquel les jeux de gorge (notamment les katajjait) constituent un genre fascinant. Plusieurs des premiers voyageurs occidentaux qui y assistèrent en firent l'expérience à leurs dépens comme nous le verrons dans les documents qui suivent. Genre fascinant aussi pour l'anthropologue en raison de sa complexité et de son ambiguïté qui le font relever à la fois du cri et du langage, du chant et de la danse, du jeu et de la musique, du rite et de la performance; en raison également et de sa dimension symbolique lorsqu'il traite du rapport à la nature, du rapport au surnaturel et du rapport homme-femme, et de sa dimension sociologique à travers la coopération nécessitée par son exécution et la compétition parfois organisée entre les exécutants.

Recherches en ethnomusicologie: les katajjait chez les Inuit du Nouveau-Québec - Montpetit, Carmen; Veillet, Céline (Études/Inuit/Studies, 1977)

Essai d’analyse d’un chant montagnais [innu] - Laplante, Louise; Maillhot, Josée (Recherches amérindiennes au Québec, 1972)

The Jesuit Relations and Allied Documents, Early Sources for an Ethnography of Music among American Indians - Crawford, David E. (Ethnomusicology, 1967)